Design of a Novel Technique for Denial of Service Attack Detection in Wireless Network - Kumar, Sanjeev; Agnihotri, Nishant (International Journal of Computer Sciences and Engineering, 2025)
There are the numbers of techniques available in the literature for the detection of denial of service attack but the effective and efficient detection of this attack in the wireless domain remains open challenges. Recently the detection of distributed denial of services attacks is the major problem in the wireless domain. In this paper, a novel technique has been designed for the detection of distributed denial of service attack in wireless networks. When sending a large scale of data to different nodes, distributed denial-of-service DDoS attacks intend the victims; consequently there is a need to implement a number of DDOS protection techniques all jointly and integrate on multiple techniques, primarily on the areas required uninterrupted service. The data and its value are unprecedented and hence cannot be ignored. This system is based on a mechanism which ensures that the fallacious information did not get injected in any kind of actual data flowing over the network. This paper has focused toward an approach which is detection of DDoS attack over a network. This mechanism works on trust generation mechanism where trust certificate is issued on the basis of training data asset comparison with the actual behavior of any node working over a network. This trust mechanism results into the detection of malicious contents and finding the intruders resulting into the attack over a network.